2020
DOI: 10.1146/annurev-economics-020320-033926
|View full text |Cite
|
Sign up to set email alerts
|

Peer Effects in Networks: A Survey

Abstract: We survey the recent, fast-growing literature on peer effects in networks. An important recurring theme is that the causal identification of peer effects depends on the structure of the network itself. In the absence of correlated effects, the reflection problem is generally solved by network interactions even in nonlinear, heterogeneous models. By contrast, microfoundations are generally not identified. We discuss and assess the various approaches developed by economists to account for correlated effects and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(42 citation statements)
references
References 108 publications
0
42
0
Order By: Relevance
“…Despite widespread public interest in understanding emotional contagion, the existing empirical knowledge is limited. Identifying the causal effect of emotional contagion has proved to be di cult because of identi cation issues such as self-selection, common shocks, and re ection 15,69 . Additionally, obtaining information on every individual in a speci c social network is usually not feasible because of data limitations.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite widespread public interest in understanding emotional contagion, the existing empirical knowledge is limited. Identifying the causal effect of emotional contagion has proved to be di cult because of identi cation issues such as self-selection, common shocks, and re ection 15,69 . Additionally, obtaining information on every individual in a speci c social network is usually not feasible because of data limitations.…”
Section: Main Textmentioning
confidence: 99%
“…If there is spillover, the bene ts of helping an individual with negative emotions could largely outweigh the cost, and undertaking interdependent interventions could be much more effective than independent individual-intervention strategies 5 .Despite widespread public interest in understanding emotional contagion, the existing empirical knowledge is limited. Identifying the causal effect of emotional contagion has proved to be di cult because of identi cation issues such as self-selection, common shocks, and re ection 15,69 . Additionally, obtaining information on every individual in a speci c social network is usually not feasible because of data limitations.…”
mentioning
confidence: 99%
“…Many studies have demonstrated how network interactions can be used to overcome the correlated effects and reflection problems. The identification of peer effects has been greatly benefited from the literature on network interactions that is fast-growing with a number of recent surveys on the topic (Bramoullé et al, 2020;Advani and Malde, 2018;Boucher and Fortin, 2016;De Paula, 2017;Blume et al, 2015). Bramoullé et al (2020) points out that the following four studies independently understood that the reflection problem is naturally solved by network interactions: Bramoullé et al (2009); De Giorgi et al (2010); Lin (2010); Laschever (2005).…”
Section: Identification Of Social Effectsmentioning
confidence: 99%
“…The identification of peer effects has been greatly benefited from the literature on network interactions that is fast-growing with a number of recent surveys on the topic (Bramoullé et al, 2020;Advani and Malde, 2018;Boucher and Fortin, 2016;De Paula, 2017;Blume et al, 2015). Bramoullé et al (2020) points out that the following four studies independently understood that the reflection problem is naturally solved by network interactions: Bramoullé et al (2009); De Giorgi et al (2010); Lin (2010); Laschever (2005). Bramoullé et al (2009) demonstrates that endogenous and contextual effects are identified through intransitive triads, that is, when peers of peers are not peers.…”
Section: Identification Of Social Effectsmentioning
confidence: 99%
See 1 more Smart Citation